2018
DOI: 10.1007/s00277-018-3232-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of partial splenic embolization for the treatment of steroid-resistant chronic immune thrombocytopenia

Abstract: Thrombopoietin-receptor agonists have been recently introduced for a second-line treatment of immune thrombocytopenia (ITP). Splenectomy has tended to be avoided because of its complications, but the response rate of splenectomy is 60-80% and it has still been considered for steroid-refractory ITP. We performed partial splenic embolization (PSE) as an alternative to splenectomy. Between 1988 and 2013, 91 patients with steroid-resistant ITP underwent PSE at our hospital, and we retrospectively analyzed the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
2
28
1
1
Order By: Relevance
“…A retrospective single-center analysis of 91 ITP patients reported an overall response rate of 84% and a 10-year failure-free survival of 52%, concluding that partial splenic embolization generates longterm durable responses (evidence level III). 209 The most common AEs included grade 1 nausea, fever, and abdominal pain. 209 This single-center experience needs confirmation.…”
Section: Laparoscopic Splenectomy Is As Effective As Openmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective single-center analysis of 91 ITP patients reported an overall response rate of 84% and a 10-year failure-free survival of 52%, concluding that partial splenic embolization generates longterm durable responses (evidence level III). 209 The most common AEs included grade 1 nausea, fever, and abdominal pain. 209 This single-center experience needs confirmation.…”
Section: Laparoscopic Splenectomy Is As Effective As Openmentioning
confidence: 99%
“…209 The most common AEs included grade 1 nausea, fever, and abdominal pain. 209 This single-center experience needs confirmation.…”
Section: Laparoscopic Splenectomy Is As Effective As Openmentioning
confidence: 99%
“…This procedure has been recently applied to the treatment of patients with refractory ITP as an alternative to splenectomy. Togasaki et al, reported that the median time to achieve the peak platelet count was 13 days after partial splenic embolization in their study on the efficacy of partial splenic embolization for patients with ITP [14]. Partial splenic embolization 14 days prior to surgery and high-dose immunoglobulin therapy just before operation resulted in increasing the platelet count >50,000/μL.…”
Section: Discussionmentioning
confidence: 99%
“…Togasaki et al who had done a study in 91 patients with steroid resistant ITP undergoing PSE found that the complete response rate (a platelet count of > 1,00,000/cumm) was found to be 51% and overall response rate was 84% (a platelet count of > 30,000/cumm). 13 Therefore, PSE could be an alternative therapy of splenectomy because it is less invasive. The cost of PSE is likely to be less than a laproscopic splenectomy.…”
Section: Discussionmentioning
confidence: 99%